Pāthakathā phisēt rư̄ang "čhariyatham khō̜ng phūdamrong tamnǣng thāng kānmư̄ang læ čhaonāthī khō̜ng rat" : nai khrōngkān sammanā "kāndamnœ̄nkān kīeokap čhariyatham khō̜ng phūdomrong tamnǣng thāng kānmư̄ang khārātchakān læ čhaonāthī khō̜ng rat tām ratthathammanūn hǣng Rātchaʻānāčhak Thai Phutthasakkarāt 2550" Wanpharưhatsabō̜dī thī 31 Karakadākhom 2551 na Rōngrǣm Mirākhœ̄n Krǣn Khō̜nwēnchan Krung Thēp Mahā Nakhō̜n (Samnak Songsœ̄m Māttrathān Čhariyatham, Samnakngān Phūtrūatkān Phǣndin, 2008)
Compilation of special speeches on ethics of the political position-holding officers and government officials, presented at a national seminar by Prof. Dr. Tanin Kraivixian, privy councillor and the 14th prime minister of Thailand.